2017
DOI: 10.1038/srep45637
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and depressive symptoms among Chinese people aged 45 and over

Abstract: We examined the controversial relationship between obesity and depression among Chinese people aged 45 and over using data from the 2013 follow-up survey of the China Health and Retirement Longitudinal Study (CHARLS). Depressive symptoms were measured using the CES-D 10; overweight and obesity were defined using WHO, Asian and Chinese criteria. The proportion of depressive symptoms was 19.9% and 33.2% in men and women, respectively. Depressive symptoms decreased as BMI increased in both men and women (P < 0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 33 publications
3
48
1
Order By: Relevance
“…Also there are some theories about the relationship between Neuropeptide Y, leptin and depression. 25,26 Depressive symptoms decreased as BMI increased in both men and women (p<0.05) in a study from China. 26 Relationship between eating disorders and other psychiatric diseases was shown in literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also there are some theories about the relationship between Neuropeptide Y, leptin and depression. 25,26 Depressive symptoms decreased as BMI increased in both men and women (p<0.05) in a study from China. 26 Relationship between eating disorders and other psychiatric diseases was shown in literature.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Depressive symptoms decreased as BMI increased in both men and women (p<0.05) in a study from China. 26 Relationship between eating disorders and other psychiatric diseases was shown in literature. For example Müller et al reported that depressive symptoms were higher in pre-bariatric patients with comorbid binge eating disorder.…”
Section: Discussionmentioning
confidence: 99%
“…BMI is converted into four attributes: "⩽18.5," "18.5-22.99," "23-24.99," and "⩾25." 31 During the preprocessing of categorical variables, all values for each variable generate new attributes, and then, each attribute has a value 1 in the column that corresponds to the true for this category and 0 otherwise. During this conversion of categorical variables, all null values are replaced with a 0.…”
Section: Data Preprocessingmentioning
confidence: 99%
“…Typical factors influencing the prevalence of depression include gender, stressful life events, and physical health problems (Qian, 2017). Gender is one of the most widely known factors of depression.…”
Section: Literature Reviewmentioning
confidence: 99%